Spatiotemporal evolution and convergence patterns of urban carbon emission efficiency in China. - Wu, Chuanqing; Deng, Heshun; Zhao, Hao; Xia, Qiwei (Humanities & Social Sciences Communications, 2025)
This paper utilizes the super-efficiency SBM-DEA model that accounts for environmentally detrimental outputs to assess urban carbon emission efficiency (UCEE) across 282 cities in China. The Dagum Gini coefficient decomposition is utilized for assessing the disparity among China's four major regions. Additionally, the non-parametric kernel density estimation (KDE) is utilized for illustrating the changing patterns of UCEE across different regions. The coefficient of variation and spatial panel model are utilized for calculating σ-convergence and β-convergence, respectively. The findings reveal a consistent decrease in UCEE across China's major geographical divisions; this difference is primarily attributed to hypervariable density. Moreover, significant disparities exist in terms of dynamic evolution characteristics of UCEE among different regions, with more pronounced urban polarization effects observed in Western China and Northeastern China. Different regions exhibit distinct convergence characteristics. The influence of economic level, industrial structure, foreign direct investment, urbanization rate, and green technology innovation on the rate of variation in UCEE exhibits notable heterogeneity.